Derivation of Performance Norms for the Jordanian Arabic Version of the Gilliam Autism Spectrum Disorder Rating Scale for Ages 3 To 13 Years (Second Edition) - Eman Alsqour, Eman; Zaza, Haidar (Jordan Journal of Educational Sciences, 2016)
This study aimed to derivative the norms for the Jordanian Arabic Version of the Gilliam Autism Rating Scale (GARS-2) which was developed it for Jordanian Environment (AL Jabery, 2008). Three types of scores: Standard score, Percentile ranks, and Autism Index (very likely, possibly, unlikely) were conducted. Study Sample consisted of 260 boys and girls(3-13 years) has been diagnosed with autism spectrum disorder at Autism Behavior Check List (ABC)and thedata collection took approximately six (6) months. Means and standard deviations has been conducted, and the normality of data was investigated by using Kolmogorov-Smirnov test (K-S). The results showed that there were no statistically significant differences on the subscale attribute to gender, which indicates the possibility of extracting uniform norms for male and female. The raw scores on the subscales convert to standard scores (M= 10; SD=3) and percentile ranks, then the sum of standard scores converted to autism average index (M= 100; SD=15). The scores on the American version comparing with the Jordanian version was very close; which indicates that these norms are valid for use in any environment if subscale "communication" has been dispensed. The study recommended further studies on development other scales for the autism spectrum disorder in the modern trends of the concept of autism spectrum disorder and its diagnosis